Children Amidst the Wave of Domestic Violence: An Analysis of Legal Protection in Indonesia Legal System - Kholik, Noor (Law Research Review Quarterly, 2021)
Domestic Violence had become a common agenda in recent decades. Some facts showed that domestic violence disproportionately affects large enough for children as victims. Violence against children is not a rare case in the community. The method used is normative research of law which is focused on the norm and also the object of law as the main data, they getting from rules and books that consist of the rule, that had to find the truth from the research that has done. The research was conducted in Yogyakarta Police. The research found that the implementation of the legal protection of children as victims of domestic violence can be done in two ways, namely the efforts of non-penal and penal efforts. Non-penal effort done by a preemptive and preventive, while the efforts made by the penal repressive actions by the police Yogyakarta after psychological violence within the domestic sphere occur and are reported to the police. Constraints faced by the police in the implementation of the legal protection of children as victims of psychological violence in the household, namely: (a) The difficulty of finding strong evidence of a child victim of psychological violence, in this case, the question is about how to form of psychological violence. (b) The difficulty to distinguish children who are experiencing emotional violence committed by family members in a household setting. A child who is experiencing violence usually has a psychological fear to reveal the problems they experienced as a result of the act of the perpetrator.